Direct oxidation of H-2 to H2O2 over PdO/Al2O3 catalysts in aqueous acidic medium: influence on H2O2 formation of Pd loading, calcination temperature and reduction of catalyst and presence of halide anions - Choudhary, Vasant R.; Jana, Prabhas (Catalysis Communications, 2008)
Effects of the Pd loading (0.2-10 wt%), calcination temperature (400-900 degrees C) and reduction of PdO/Al2O3 on its performance in the H-2-to-H2O2 oxidation (with H-2/O-2 = 1:1) in an aqueous 0.1 M H3PO4 medium, in the absence and presence of different halide anions, under ambient conditions have been investigated. The effect of calcination temperature on the H2O2 formation varied depending upon the Pd loading. The influence of the different halide anions was found to depend strongly on the nature of halide anion (F-, Cl-, Br- or I-) and the oxidation state of Pd and its loading in the catalyst. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: halide catalyst promoters; Hydrogen peroxide; oxidation of H-2 to H2O2; Pd/Al2O3; PdO/Al2O3